Activity-Dependent Synaptic Refinement: New Insights from Drosophila - Vonhoff, Fernando; Keshishian, Haig (Frontiers in Systems Neuroscience, 2017)
During development neurons establish inappropriate connections as they seek out their synaptic partners, resulting in supernumerary synapses that must be pruned away. The removal of miswired synapses usually involves electrical activity, often through a Hebbian spike-timing mechanism. A novel form of activity-dependent refinement is used by Drosophila that may be non-Hebbian, and is critical for generating the precise connectivity observed in that system. In Drosophila, motoneurons use both glutamate and the biogenic amine octopamine for neurotransmission, and the muscle fibers receive multiple synaptic inputs. Motoneuron growth cones respond in a time-regulated fashion to multiple chemotropic signals arising from their postsynaptic partners. Central to this mechanism is a very low frequency (<0.03Hz) oscillation of presynaptic cytoplasmic Ca, that regulates and coordinates the action of multiple downstream effectors involved in the withdrawal from off-target contacts. Low frequency Ca oscillations are widely observed in developing neural circuits in mammals, and have been shown to be critical for normal connectivity in a variety of neural systems. In Drosophila these mechanisms allow the growth cone to sample widely among possible synaptic partners, evaluate opponent chemotropic signals, and withdraw from off-target contacts. It is possible that the underlying molecular mechanisms are conserved widely among invertebrates and vertebrates.